In vitro evaluation of antioxidant activity of methanolic extracts obtained from seaweeds endemic to the coast of Ceará, Brazil - Lima, Rebeca Larangeira; Pires-Cavalcante, Kelma Maria dos S.; Alencar, Daniel Barroso; Viana, Francisco Analdo; Sampaio, Alexandre Holanda; Saker-Sampaio, Silvana (Acta Scientiarum. Technology, 2016)
The aim of the present research was to evaluate the antioxidant activity of six species of marine algae (Caulerpa cupressoides, Ulva fasciata, Amansia multifida, Cryptonemia crenulata, Dictyota dichotoma and Sargassum vulgare) collected in 2011 at Paracuru Beach, Ceará State, Brazil. Methanol extracts were prepared from oven-dried algae and used to measure total phenolic content (TPC) using the Folin- Ciocalteu colorimetric method. In vitro antioxidant activity of the algal extracts (12.5 to 100 mg mL-1) was analyzed by DPPH radical scavenging, ferric-reducing antioxidant power (FRAP) and ferrous ion chelation (FIC). BHA and EDTA were used as positive controls. Based on the standard curve of gallic acid, TPC values ranged from 10.49 to 19.94 mg gallic acid equivalents (GAE) g-1 of extract. DPPH results of algal extracts at all concentrations tested remained between 53.96 and 64.96%, lower than the positive control (BHA). All species showed little FRAP activity (less than 0.1) when compared to BHA. FIC above 20% was detected only in the extract from U. fasciata (100 mg mL-1), while all the others had activities below 17%. The activity of EDTA ranged from approximately 48 (12.5 mg mL-1) to 98% (100 mg mL-1). These results allow us to consider the algae species studied as potentially promising sources of natural antioxidants. Â 